Patient‐centredness in acute stroke care – a qualitative study from the perspectives of patients, relatives and staff. (25th May 2020) - Busetto, L.; Stang, C.; Hoffmann, J.; Amiri, H.; Seker, F.; Purrucker, J.; Ringleb, P. A.; Nagel, S.; Bendszus, M.; Wick, W.; Gumbinger, C.; ,
Abstract : Background and purpose: Although patient‐centredness is considered a key component of high‐quality neurological care, it is unclear to what extent it can or should be implemented during the acute phase. Using acute stroke as an example, the aim was to identify critical junctures for patient‐centredness along the acute care pathway from the perspectives of patients, relatives and staff. Methods: A qualitative multi‐method study was conducted including 27 non‐participant observations and 37 semi‐structured interviews with patients, relatives and staff. Junctures were defined as critical when mentioned (as problematic) in two or three information sources (i.e. observations, staff interviews, or patient and relative interviews), as potentially critical when mentioned in one, and as uncritical when not mentioned. Results: Post‐procedure communication after thrombectomy, patients' stay at the stroke unit and decision‐making around transfer, discharge and rehabilitation were identified as critical junctures for patient‐centredness. Arrival at the emergency department and the (thrombectomy) treatment itself were identified as uncritical junctures, whilst history‐taking and treatment preparation, the treatment decision and patients' stay at the intensive care unit were identified as potentially critical junctures. Conclusions: In acute stroke care, patients, relatives and staff prioritize fast over patient‐centred decision‐making in the most time‐critical phases, especially before and during treatment. This is reversed after the procedure, when difficulties arise implementing a patient‐centred approach in clinical practice. To improve patient‐centredness where it is most needed, clear guidelines and accessible resources are recommended. Future research should investigate whether insights from acute phases of stroke care are applicable to other neurological conditions as well.